Design, Synthesis, and Acaricidal Activities of Novel Pyrazole Acrylonitrile Compounds. (13th July 2016) - Huang, Danling; Huang, Mingzhi; Liu, Aiping; Liu, Xingping; Liu, Weidong; Chen, Xiaoyang; Xue, Hansong; Sun, Jiong; Yin, Dulin; Wang, Xiaoguang
Abstract : Using cyenopyrafen as the lead compound, a series of novel pyrazole acrylonitrile compounds were designed and synthesized via the reaction of butylphenylacetonitrile with the corresponding (substituted pyrazol‐5‐yl) methanone of pyrethroid alcohols in the presence of potassium tert‐butoxide. These compounds showed prominent acaricidal activity against Tetranchus urticae . In particular, IIf, IIh, IIo, andIIp displayed excellent activities, which the median lethal concentrations were all lower 0.4 mg/L. In addition, thestructure‐activity relationship for the target compounds was discussed. Abstract :